Evaluation of post-swallow residue with visual analysis of swallowing efficiency and safety in patients with idiopathic parkinson's disease - ENVER, NECATİ (My University, 2023)
Objectives: Dysphagia is common in idiopathic Parkinson’s disease (IPD) and is associated with impairments in both swallowing safety and swallowing efficiency. The goals of this study were to define post-swallow residue patterns in people with IPD and describe pathophysiological endoscopic findings affecting residue accumulation. Methods: This was a prospective single-blinded cross-sectional cohort study of patients with the diagnosis of IPD recruited from a Movement Disorder Clinic. Clinical variables included patient age, cognitive function, and measures of disease severity, and laryngoscopic examinations with a flexible endoscopic evaluation of swallowing (FEES) were completed for each patient. Visual Analysis of Swallowing Efficiency and Safety (VASES) was used to analyze FEES. Post-swallow residue outcomes and non-residue endoscopic outcomes including the Bowing index, Penetration Aspiration Scale (PAS) score, premature leakage, and build-up phenomenon were evaluated. Multiple regression models were used to evaluate factors affecting the residue at different anatomic levels. Results: Overall 53 patients completed the study. The multiple regression analyses showed a relation between (1) the presence of residue at the level of oropharynx and epiglottis with premature leakage, (2) the presence of residue at the level of the laryngeal vestibule and vocal folds with build-up phenomenon, and (3) the presence of residue at the level of the hypopharynx, laryngeal vestibule, and subglottis with airway invasion. Conclusion: Residue pattern during FEES is associated with specific swallow dysfunctions in IPD. Using residue localization and quantification may be a helpful tool in assessing the impact of targeted swallowing interventions in patients with IPD and dysphagia.
Keywords: dysphagia; idiopathic Parkinson’s disease; functional endoscopic evaluation of swallowing; Visual Analysis of Swallowing Efficiency and Safety; post-swallow residue